Visible and near-infrared observations of interstellar comet 2I/Borisov with the 10.4-m GTC and the 3.6-m TNG telescopes. Issue 2 (30th April 2020) - de León, J; Licandro, J; de la Fuente Marcos, C; de la Fuente Marcos, R; Lara, L M; Moreno, F; Pinilla-Alonso, N; Serra-Ricart, M; De Prá, M; Tozzi, G P; Souza-Feliciano, A C; Popescu, M; et al.
ABSTRACT: In this work, we present the results of an observational study of 2I/Borisov carried out with the 10.4-m Gran Telescopio Canarias (GTC) and the 3.6-m Telescopio Nazionale Galileo (TNG), both telescopes located at the Roque de Los Muchachos Observatory, in the island of La Palma (Spain). The study includes images in the visible and near-infrared, as well as visible spectra in the 3600–9200 Å wavelength range. N -body simulations were also performed to explore its orbital evolution and Galactic kinematic context. The comet's dust continuum and near-infrared colours are compatible with those observed for Solar system comets. From its visible spectrum on the nights of 2019 September 24 and 26, we measured CN gas production rates Q (CN) = (2.3 ± 0.4) × 10 24 mol s −1 and Q (CN) = (9.5 ± 0.2) × 10 24 mol s −1, respectively, in agreement with measurements reported by other authors on similar nights. We also obtained an upper limit for the C2 production rate of Q (C2 ) < (4.5 ± 0.1) × 10 24 mol s −1 . Dust modelling results indicate a moderate dust production rate of ∼50 kg s −1 at heliocentric distance r h = 2.6 au, with a differential power-law dust size distribution of index ∼–3.4, within the range reported for many comet comae. Our simulations show that the Galactic velocity of 2I/Borisov matches well that of known stars in the solar neighbourhood and also those of more distant regions of the Galactic disc.